Establishment and assessment of a nomogram model for predicting the risk of fulminant myocarditis: A STROBE compliant cross-sectional study. Issue 17 (30th April 2021) - Xu, Guifen; Chen, Feizhen; Zhao, Wenxiang; Zheng, Yong; Zhuang, Wei; Yu, Fuling
Abstract : Abstract: We aimed to identify potential clinical predictors associated with the risk of fulminant myocarditis, and further to establish and assess a nomogram model based on significant attributes for clinical practicability. This is a retrospective, cross-sectional study, involving 28 patients with fulminant myocarditis and 35 age-, and sex-matched patients with non-fulminant myocarditis. Effect-size estimates are expressed as odds ratio (OR) and 95% confidence interval (CI). Fifteen factors were primarily identified to be associated with the significant risk of fulminant myocarditis after adjusting for confounders. Due to strong correlation, 6 factors were retained, including mean arterial pressure (OR, 95% CI, P : .82, .72–.94, .005), creatinine (2.15, 1.13–4.10, 0.020), blood urea nitrogen (1.45, 1.04–2.02, 0.028), aspartate aminotransferase (2.62, 1.16–5.91, 0.021), troponin I (1.43, 1.07–1.90, 0.015), and ventricular wall motion abnormality (25.81, 2.52–264.69, 0.006). The contribution of the 6 significant factors to predicting fulminant myocarditis risk was significant from multi-angle analyses, and regressing these factors in a nomogram model exhibited good predictive accuracy, as reflected by both C -index (>90%, P < .001). We have identified 6 clinical factors in significant association with fulminant myocarditis, and their prediction capability was more obvious in a nomogram model. Further investigations with larger sample sizes and longer follow-up intervals are warranted. Abstract : Supplemental Digital Content is available in the text